Obstacles to adopting a healthy lifestyle among primary healthcare patients at King Abdulaziz Medical City in Riyadh, Saudi Arabia - Mohammed Aldosari; Abdulrahman Alghamdi; Saad Alsulaiman; Abdullah Alqahtani; Fahad Alenizy; Nawaf Alsufyani; Abdullah Alghamdi (Saudi Journal for Health Sciences, 2024)
Background: Noncommunicable diseases (NCDs) are a significant concern for global health as they significantly contribute to mortality and morbidity. In Saudi Arabia, NCDs account for a substantial portion of deaths. Understanding barriers to adopting a healthy lifestyle is crucial for effective prevention and management. The study aims to identify barriers to physical activity and healthy eating to inform targeted interventions that promote healthier behaviors and reduce the burden of NCDs in this population. Aim: This study aims to determine the barriers to healthy lifestyle among patients attending primary health-care clinics in King Abdulaziz Medical City (KAMC) in Riyadh city, Saudi Arabia. Settings and Design: This is a cross-sectional study; data were collected from January 2023 to July 2023. This study was conducted in three main primary health-care centers (Khashm-Ala’an, Umm-alhammam, and Iskan) of KAMC, Riyadh. Methods: A quantitative cross-sectional study was conducted in Riyadh city. The study utilized a questionnaire adapted from previous research. Results were considered significant when the P < 0.05. Results: The study included 383 participants aged 15 to over 45 years, with a significant proportion in the 15–29 years of age group. Approximately half were male, with the majority having attained a university education or higher. A considerable portion had never been married and reported incomes below 10,000 SR per month. Physical inactivity affected nearly half of the participants, primarily attributed to a lack of willpower, followed by factors such as lack of energy and time constraints. Barriers to a healthy diet mirrored those of physical activity, with lack of willpower and time being prominent factors. These barriers exhibited various associations with demographic variables such as age, gender, education, marital status, and income. Conclusion: With 383 participants, the study skewed toward young, educated, unmarried individuals with lower incomes. While nearly half reported physical inactivity and unhealthy diets, citing lack of willpower and time constraints as primary reasons, further analysis is needed to explore how these barriers connect with the diverse demographic makeup of the study population.